Analisis Financial Distress pada Perusahaan Tambang Batubara pada Tahun 2016 – 2022 dengan Struktur Modal Sebagai Variabel Intervening - Muhamad Dzikri Pratama Akmaludin; Ferikawita M. Sembiring (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Purpose of this research is to examine whether the coal companies that registered at Indonesian Stock Exchange is under distress condition or notand also to analyze the factors that affecting it. Variables used in this research were Return on Asset (ROA), Current Ratio (CR), Total Asset Turnover (TATO) and Cash Flow Operation and Capital Structure respectively as Intervening Variable. The research concluded using 22 sample of coal companies that registered under Indonesian Stock Exchange. The result of this research yielded that Return on Asset, Current Ratio and Total Asset Turnover affecting Financial Distress. Total Asset Turnover affecting Capital Structure and Total Asset Turnover able to mediate the independent variable and its dependent variable thus and indirectly Current Ratio and Total Asset Turnover affecting Financial Distress through Capital Structure. Keywords: Financial Distress, Capital Structure, ROA, Current Ratio, Total Asset Turnover